2007
DOI: 10.1007/s00467-006-0304-2
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin serum levels in children undergoing chronic haemodialysis

Abstract: Infections account for considerable morbidity and mortality in patients requiring haemodialysis (HD). Procalcitonin (PCT)-a low molecular weight protein of 13 kDa-helps one to distinguish viral from bacterial infections and to evaluate the severity of bacterial infections. We investigated (1) PCT baseline levels in eight children undergoing chronic HD with high-flux membranes and (2) changes in the serum levels of PCT, C-reactive protein (CRP) and beta-2-microglobulin (beta2-MG)-a peptide with biochemical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Currently applied laboratory parameters for inflammation can be misleading-some of these parameters may be decreased, such as white blood cell count, and others may be non-specifically increased, such as erythrocyte sedimentation rate, C-reactive protein (CRP), or procalcitonin (PCT) [7][8][9]. In this study, we investigated plasma calprotectin as an inflammatory marker in chronically hemodialyzed ESRD patients.…”
mentioning
confidence: 99%
“…Currently applied laboratory parameters for inflammation can be misleading-some of these parameters may be decreased, such as white blood cell count, and others may be non-specifically increased, such as erythrocyte sedimentation rate, C-reactive protein (CRP), or procalcitonin (PCT) [7][8][9]. In this study, we investigated plasma calprotectin as an inflammatory marker in chronically hemodialyzed ESRD patients.…”
mentioning
confidence: 99%
“…We must mention that increases of PCT are noticed in several non-infectious conditions, such as acute myocardial infarction, major surgery, burns, and shock, as well as in dialysis patients. [17,19,[26][27][28] Their influence on the results of our study must be small (if any exists at all), as most of these conditions are easily recognized and did not occur in our patients, and the referred increases are small (mostly less than the defined 1.5 ng/mL upper limit of normal for PCT).…”
Section: Discussionmentioning
confidence: 83%
“…According to Rahimzadeh et al [26], serum procalcitonin concentration is a sensitive and promising predictor of high-grade vesicoureteral reflux (VUR). Also, Lorton et al [27] concluded that increase of serum PCT in children with severe bacterial infections is mostly massive (10-fold to 1,000-fold), indicating a low risk for false negative results in these patients. Lastly, the study by Decaluwe et al [28] revealed that serum levels of PCT are associated with the severity of illness in children with diarrhea-associated hemolytic uremic syndrome.…”
Section: Discussionmentioning
confidence: 99%